2022
DOI: 10.35848/1347-4065/ac7ea8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu addition on rapid solid-state crystal growth of (K,Na)NbO3 single crystals

Abstract: We investigated the effects of 0.5 mol% to 6.0 mol% CuO addition on crystal growth by the rapid solid-state crystal growth method to synthesize large unitary rectangular (K,Na)NbO3 (KNN) single crystals several square centimeters within 24 h. X-ray photoelectron spectroscopy and X-ray powder diffraction measurements revealed that CuO and Cu2O segregated in the region near the coarsened single crystal/polycrystal boundary. A positive correlation between crystal growth and the addition of CuO up to 1.5 mol% was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In these black regions, the liquid phase of CuO segregated from the enlarged crystal nucleus should have formed during firing, promoting the continued growth of single crystals. 23) The firing temperature ranges for the growth of the large unitary single crystals were 1020 °C-1025 °C, 1045 °C-1055 °C, and 1060 °C-1065 °C for a = 0.50 wt%, 0.55 wt%, and 0.60 wt%, respectively. When the heating temperatures were higher than the abovementioned values, large unitary single crystals were not obtained because of the simultaneous growth of many irregularly shaped single crystals from multiple growth nuclei.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In these black regions, the liquid phase of CuO segregated from the enlarged crystal nucleus should have formed during firing, promoting the continued growth of single crystals. 23) The firing temperature ranges for the growth of the large unitary single crystals were 1020 °C-1025 °C, 1045 °C-1055 °C, and 1060 °C-1065 °C for a = 0.50 wt%, 0.55 wt%, and 0.60 wt%, respectively. When the heating temperatures were higher than the abovementioned values, large unitary single crystals were not obtained because of the simultaneous growth of many irregularly shaped single crystals from multiple growth nuclei.…”
Section: Resultsmentioning
confidence: 99%
“…However, as described above, most of the Cu ions were excluded from the crystal grains during the crystal growth process via the RSSCG method, and only a small amount of Cu ions remained in the crystal grains. 23) As described below, oxygen vacancies in the KNN system materials were detected as defect complexes with Cu through ESR analysis. Because a very small amount of Cu ions rather than the density of oxygen vacancies may dominate the formation of defect complexes in the KNN crystal grains, annealing the calcined powder below the temperature at which the RSSCG method occurs is desirable for accurately comparing the concentration of oxygen vacancies among the calcined powders.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for this poor repeatability is not currently known. The size of the single crystals may be improved by choice and optimization of different sintering additives, as carried out for KNN [32,72,73]. In recent work in our laboratory, it has been found that use of a Ba(Cu 0.13 Nb 0.66 )O 3 additive and a [001]-oriented KTaO 3 seed crystal allowed growth of a large and dense single crystal of (K 0.5 Na 0.5 )NbO 3 , although problems with repeatability persisted [49].…”
Section: Resultsmentioning
confidence: 99%